Rose Pests and Diseases in Florida - Gary W. Knox; Mathews Paret; Russell F. Mizell (EDIS)
Roses are one of the most popular flowering shrubs in Florida and the United States. Valued for their beautiful and often fragrant blooms, roses have been cultivated in gardens for centuries as vines. Roses can grow and flower 9 months of the year in North Florida and year-round in the rest of Florida. Roses have become especially popular in recent years with the introduction of Knock Out® and other shrub roses. Unfortunately, increased use and misuse of roses have resulted in more reports of pest problems. This revised 9-page fact sheet was written by Gary W. Knox, Mathews Paret, and Russell F. Mizell, III, and published by the UF Department of Environmental Horticulture, January 2012.